Renal and Neurological Response with Eculizumab in a Patient with Transplant Associated Thrombotic Microangiopathy after Allogeneic Hematopoietic Progenitor Cell Transplantation - Ömür Gökmen Sevindik; İnci Alacacıoğlu; Abdullah Katgı; Şerife Medeni Solmaz; Celal Acar; Özden Pişkin; Mehmet Ali Özcan; Fatih Demirkan; Bülent Ündar; Güner Hayri Özsan (Case Reports in Hematology)
Transplantation-associated thrombotic microangiopathy (TA-TMA) is a challenge after allogeneic hematopoietic progenitor cell transplantation, considering the diagnostic uncertainties and lack of established treatment. We report a 43-year-old male patient who was diagnosed as TA-TMA after allogeneic progenitor cell transplantation for a progressive ALK negative anaplastic large cell lymphoma and responded to eculizumab with dramatically improving neurological status and renal function. Rapid neurological and renal recovery achieved after eculizumab could support a possible relationship between complement activation and TA-TMA. Eculizumab should be a reasonable treatment approach in patients with TA-TMA after allogeneic hematopoietic progenitor cell transplantation.